BIOMASS IN Eucalyptus spp. STANDS IN SMALL RURAL PROPERTIES IN VERA CRUZ, RS - Mauro Valdir Schumacher; Rudi Witschoreck; Francine Neves Calil (Ciência Florestal, 2011)
The study was conducted in 2, 4, 6 and 8 year-old Eucalyptus spp. stands, in the municipality of Vera Cruz, RS. The eucalyptus biomass sampling consisted of felling 24 trees, 6 trees per age, distributed in three diametric classes. The understory and litter compartments were also sampled. The estimated biomass was 26.70; 44.55; 192.67 and 232.93 Mg ha-1 in eucalyptus; 1.87; 1.97; 4.37 and 8.24 Mg ha-1 in understory and 4,05; 5,98; 11,80 and 12,28 Mg ha-1 in the litter, totaling 32.62; 52.50; 208.84 and 253.45 Mg ha-1, respectively, in 2, 4, 6 and 8 year stands. Except for the wood, all the other components of eucalyptus trees showed a decrease in relative biomass with the increase of age.